Marketing Dynamics of Grapes in Pune Division: Channels, Efficiency, and Stakeholder Issues - , Dashant R. Dhoriyani, Mahesh R. Prajapati (Archives of Current Research International, 2024)
India emerging as the world's second-largest producer of fruits and vegetables. Farmers who produce agricultural products are spread over distant communities whereas customers live in semi-urban or urban areas. This produce must reach consumers for final usage and consumption. This product passes via various agencies and functionaries before reaching the consumer. The study objective is to identify different marketing channels of Grapes, estimate the price spread and marketing efficiency of identified channels, and identify Problems faced by different stakeholders. Primary data were collected through 60 farmers and 30 intermediaries. A descriptive study design with a non-probability sampling method and purposive sampling technique was employed. Tabular, percentage and Garrett ranking methods were utilized for data analysis to obtain the desired results. From this study, four marketing Channels were found namely Channel I (Farmer – village trader- wholesalers cum commission agents - Retailer - Consumer), Channel II (Farmer – pre-harvest contractor- wholesalers cum commission agents - Retailer - Consumer), Channel III (Farmer -Wholesaler cum commission agent - Retailer – Consumer) and Channel IV (Farmer - Company CC - Company DC - Consumer. Channel III stands out with the highest producer's share in the consumer's rupee (62.43%) and the highest marketing efficiency (1.66). The majority of farmers faced the challenge of high costs incurred for the purchase of inputs and for the transportation of produce. The quality variation was a major problem faced by village traders. Price fluctuation was a major problem faced by pre-harvest contractors. Facing competition from other private players was a major problem for private companies. Quality variation was a major problem for the wholesaler cum commission agent. Retailers' major problems were price fluctuation followed by high transportation costs.